Fermentation of Livestock Blood Waste as Fish Feed Ingredient - Andriani, Yuli; Dipatiguna, Siti Nisrina Ulfah; Putra, Vito Dwisetia; Prasadi, Marsel; Aisyah, Aisyah (Journal of Coastal and Ocean Sciences, 2025)
Livestock blood waste has significant potential to be utilized as an alternative feed ingredient due to its high protein content, reaching up to 80%, and abundant availability. However, blood waste is known to contain high levels of iron and an imbalanced amino acid profile. Based on these issues, one potential solution is to ferment livestock blood waste to enhance its nutritional value. This review article aims to compile and analyze various effective fermentation methods and identify best practices in the fermentation process of livestock blood waste. Fermentation can be carried out using various microbes, mainly lactic acid bacteria. Fermentation treatment of livestock blood waste with lactic acid bacteria using lactic acid concentrations ranging from 3% to 6% produces blood waste with a well-balanced nutritional profile. Meanwhile, the optimal use of blood waste as an alternative feed ingredient for fish is achieved by adding formic and propionic acids at doses of 1.5%–3%, improving fish protein digestibility by 94.66%. This indicates that livestock blood waste can be an alternative raw material in fish feed production